Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kepuasan Kerja Pegawai Kementerian Sosial RI - Widhyani, Reghita Ayu; Murniyati (CV Warnak Johanna Nusantara, 2026)
This study aims to determine the effect of work environment and work motivation on employee job satisfaction at the Ministry of Social Affairs of the Republic of Indonesia. The research used a quantitative approach with multiple linear regression analysis. The sample consisted of 35 employees selected using a saturated sampling technique. Data were collected through questionnaires with a Likert scale. The results indicate that, partially, the work environment variable has no significant effect on job satisfaction, while the work motivation variable has a positive and significant effect. Simultaneously, both independent variables significantly affect job satisfaction with a contribution of 39.1%, while the remaining 60.9% is influenced by other factors beyond this study. These findings reveal that work motivation is the dominant factor influencing employee satisfaction, while the work environment serves as a supporting factor. This research is expected to contribute to the development of human resource management knowledge and serve as a reference for government institutions in formulating motivation and workplace improvement policies.